Reconciliation and Peace Opportunity: A Peace Psychology Analysis on Venezuela Crisis - Umar Mubdi (Department of International Relations, University of Mataram, 2020)
The Venezuela crisis is an intersection between political turmoil, economic crisis, mismanagement of natural resources, poverty, and health issues. The root causes of the crisis can be examined by using a peace psychology analysis, chiefly the concept of moral disengagement. This perspective is useful for looking at the Venezuelan crisis in a different approach and, at the same time, addressing peace efforts. One of the things that need to be pursued by domestic actors and humanitarian intervention is reconciliation. This reconciliation must meet the pre-conditions for the dialogue and peace agenda.